Bifunctional gypsum admixture based on plant polyphenol-nanoparticles and preparation method thereof
By using a dual-function admixture to wrap metal oxide nanoparticles in gypsum, the shortcomings of gypsum in X-ray shielding performance and processability are solved, and efficient X-ray shielding and extended solidification time are achieved.
Patent Information
- Application Number
- CN202510221745.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-27
AI Technical Summary
Existing gypsum materials have shortcomings in X-ray shielding performance and processability, especially when doping rare earth elements, it will accelerate the condensation of gypsum, affecting processing and application.
Using a bifunctional gypsum admixture based on plant polyphenols-nanoparticles, the dispersion and stability of nanoparticles are improved by wrapping plant polyphenols on the surface of metal oxide nanoparticles, thereby enhancing the X-ray shielding performance of gypsum, and forming a stable complex with the Ca2+ in the gypsum slurry, delaying the solidification time of gypsum.
It realizes efficient shielding of X-rays by gypsum, and at the same time extends the initial settling time of gypsum, improves the plasticity of gypsum, and solves the problems of uneven dispersion of nanoparticles and unstable loads.
Smart Images

Figure CN119684029A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building material admixtures, in particular to a dual-functional gypsum admixture based on plant polyphenols-nanoparticles and a preparation method thereof. Background Art
[0002] X-rays are widely used in medical imaging, radiotherapy, non-destructive testing and other fields. However, the widespread use of X-rays has brought about a series of safety issues and put forward higher requirements on the performance of protective materials. Currently commonly used shielding materials such as lead plates and lead-containing plexiglass have excellent shielding properties against X-rays. However, lead materials have the disadvantages of high density, high toxicity and low strength, and also have the problem of poor absorption of X-rays with energies between 40-90 keV. Therefore, it is urgent to develop new materials with X-ray shielding properties to reduce the safety hazards brought by X-rays.
[0003] The mechanism of shielding X-rays is achieved by the photoelectric effect and Compton effect between radiation photons and matter. Among them, the photoelectric effect refers to the elastic collision between radiation photons and the extranuclear electrons of matter, so that most of the energy of the photons is absorbed by the electrons. The Compton effect refers to the inelastic collision between radiation photons with higher energy and electrons, so that most of the energy of the photons is transferred to the electrons. Rare earth elements have a high probability of photoelectric effect and Compton effect with radiation photons due to their high atomic number and special optical, electrical and magnetic properties, thus having excellent shielding performance against X-rays. Therefore, the preparation of new materials containing rare earth elements with high atomic numbers is expected to achieve efficient shielding of X-rays.
[0004] Building gypsum is a commonly used inorganic building material, which is widely used due to its advantages such as light weight, high strength and low production cost. However, the short setting time (5-10 min) greatly limits the plasticity and transportation efficiency of the gypsum itself. Simply doping gypsum with rare earth elements can improve the X-ray shielding performance of gypsum-based materials, but it will further accelerate the setting of gypsum, which is more unfavorable for the subsequent processing and application of gypsum-based materials.
[0005] In summary, how to give gypsum higher X-ray shielding performance and improve its processability is an urgent problem to be solved. Summary of the invention
[0006] The purpose of the present invention is to provide a dual-functional gypsum admixture based on plant polyphenols-nanoparticles and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.
[0007] To achieve the above object, the present invention provides the following solutions:
[0008] One of the technical solutions of the present invention is to provide a method for preparing a dual-functional gypsum admixture based on plant polyphenols-nanoparticles, the steps comprising:
[0009] Plant polyphenols are added to the metal oxide nanoparticle dispersion, the pH is adjusted to 7.5-8.0, and after the reaction, the dual-functional gypsum admixture is obtained by filtering, washing and drying.
[0010] Furthermore, the metal oxide nanoparticles in the metal oxide nanoparticle dispersion include at least one of erbium oxide nanoparticles, bismuth oxide nanoparticles, tungsten oxide nanoparticles, lanthanum oxide nanoparticles, tin oxide nanoparticles and cesium oxide nanoparticles.
[0011] Preferably, the particle size of the metal oxide nanoparticles is 50-200 nm.
[0012] Furthermore, the concentration of the metal oxide nanoparticles in the metal oxide nanoparticle dispersion is 5-10 wt %.
[0013] Furthermore, the metal oxide nanoparticle dispersion is prepared by dispersing metal oxide nanoparticles in water.
[0014] Furthermore, the plant polyphenols include tannic acid, gallic acid or catechin acid.
[0015] Furthermore, the concentration of the plant polyphenols in the reaction system is 0.03-0.05 mol / L.
[0016] Furthermore, the pH is adjusted to 7.5-8.0 by using PBS buffer.
[0017] Furthermore, the reaction temperature is 60-80°C, the reaction time is 5-8 h, and the reaction speed is 2000 r / min.
[0018] Furthermore, the washing is washing with water at least twice.
[0019] Furthermore, the drying temperature is 40-60°C and the drying time is 8-12 h.
[0020] The second technical solution of the present invention is to provide a dual-functional gypsum admixture obtained by the above-mentioned preparation method.
[0021] The third technical solution of the present invention is to provide an application of the above-mentioned dual-functional gypsum admixture in the preparation of gypsum.
[0022] Technical solution 4 of the present invention: Provide an X-ray shielding gypsum, which comprises, by mass percentage:
[0023] 50~90% gypsum powder and 10~50% of the above dual-functional gypsum admixture.
[0024] The present invention introduces metal oxide nanoparticles into gypsum-based materials by adding admixtures, so that when the radiation photons penetrate the gypsum, they effectively collide with the nanoparticles in the gypsum-based materials, thereby achieving efficient shielding of the radiation. At the same time, plant polyphenols are coated on the surface of the metal oxide nanoparticles based on the action of π-π bonds. There are multiple intermolecular forces between the nanoparticles coated with plant polyphenols, thereby enhancing the dispersibility and stability of the nanoparticles, solving the problems of uneven dispersion and unstable loading when the metal oxide nanoparticles are directly loaded on the substrate, and increasing the probability of effective collision between the radiation photons and the nanoparticles, thereby improving the shielding performance of the material. Since when metal oxides are directly doped with gypsum, the coagulation speed of gypsum will be accelerated, which is not conducive to the subsequent processing and application of gypsum-based materials. There are a large number of phenolic hydroxyl groups in the plant polyphenols. By coating the metal oxides, these phenolic hydroxyl groups can react with Ca in the gypsum slurry when the metal oxides are coated. 2+ The formation of a stable complex reduces free Ca 2+ concentration, thereby slowing down the crystallization process of CaSO4·2H2O. This complexation will slow down the hydration reaction rate of gypsum and prolong the setting time of gypsum.
[0025] The present invention discloses the following technical effects:
[0026] The present invention provides a method for preparing a bifunctional gypsum admixture based on plant polyphenols-nanoparticles. The plant polyphenols-nanoparticle bifunctional gypsum admixture is obtained by encapsulating the surface of metal oxide nanoparticles with plant polyphenols. The preparation method is simple, the conditions are mild, and it is easy to apply on a large scale. At the same time, it has the characteristics of being easy to use, efficient, and multifunctional.
[0027] The gypsum admixture provided by the present invention can delay the setting time of gypsum and increase the plasticity time of gypsum slurry. After introducing 10-50% of the admixture based on the mass of gypsum, the initial setting time of gypsum is extended to 20-80 min. At the same time, the gypsum can achieve efficient shielding of X-rays, and solve the problem that metal oxide nanoparticles cannot be uniformly and stably loaded on gypsum crystals. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 The SEM images of gypsum after adding different proportions of admixtures of Example 3 and Example 4;
[0030] Figure 2 In the figure, a is the Fourier infrared spectrum of erbium oxide nanoparticles before and after modification with tannic acid, b is the X-ray diffraction pattern of erbium oxide nanoparticles before and after modification with tannic acid, c is the TSI value of nanoparticles dispersed in water for one hour before and after modification, and d is the digital photo of the aqueous dispersion of nanoparticles after standing for 8 hours before and after modification;
[0031] Figure 3 TEM images of Example 3, wherein a is BF-TEM and b is HAADF-STEM;
[0032] Figure 4 TEM images of Example 4, wherein a is BF-TEM and b is HAADF-STEM;
[0033] Figure 5 This is a schematic diagram of a radiation shielding efficiency test device;
[0034] Figure 6 is the X-ray shielding efficiency of the gypsum to which the admixtures of Examples 1 to 4 are added, wherein a is Example 1, b is Example 2, c is Example 3, and d is Example 4;
[0035] Figure 7 is the X-ray shielding efficiency of the gypsum added in Example 1 and Comparative Example 1, wherein a is an addition amount of 10%, b is an addition amount of 30%, and c is an addition amount of 50%;
[0036] Figure 8 is the X-ray shielding efficiency of the gypsum added in Example 3 and Comparative Example 2, wherein a is an addition amount of 10%, b is an addition amount of 30%, and c is an addition amount of 50%;
[0037] Fig. 9 is the X-ray shielding efficiency of the gypsum with the admixtures of Examples 5 to 8, wherein a is Example 5, b is Example 6, c is Example 7, and d is Example 8;
[0038] Fig.10 is the X-ray shielding efficiency of the gypsum added in Example 5 and Comparative Example 3, wherein a is an addition amount of 10%, b is an addition amount of 30%, and c is an addition amount of 50%;
[0039] Fig.11 The X-ray shielding efficiency of the gypsum added in Example 7 and Comparative Example 4, wherein a is an addition amount of 10%, b is an addition amount of 30%, and c is an addition amount of 50%. DETAILED DESCRIPTION
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0041] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] The raw materials and reagents used in the specific embodiments of the present invention are all commercially available products.
[0046] Example 1
[0047] The preparation steps of the bifunctional gypsum admixture based on plant polyphenols-nanoparticles are as follows:
[0048] S1. Add 10 g of nano-erbium oxide with a particle size of 200 nm into a reactor, then add 50 mL of deionized water, and stir ultrasonically at room temperature for 30 min to obtain a nano-erbium oxide dispersion;
[0049] S2. Add 50 mL of 0.03 mol / L tannic acid solution to the reactor of step S1, and use phosphate buffer to adjust the pH of the reaction system to 8.0, then heat to 60°C, stir and react at a speed of 2000 r / min for 5 h. After the reaction is completed, filter, then wash the solid product twice with deionized water to remove unloaded polyphenol compounds, and finally dry at 60°C for 12 h to obtain a bifunctional gypsum admixture.
[0050] Example 2
[0051] Compared with Example 1, the only difference is that 50 mL of 0.03 mol / L tannic acid solution is replaced with 50 mL of 0.03 mol / L gallic acid solution.
[0052] Example 3
[0053] Compared with Example 1, the only difference is that the particle size of the nano-erbium oxide is 50 nm.
[0054] Example 4
[0055] The preparation steps of the bifunctional gypsum admixture based on plant polyphenols-nanoparticles are as follows:
[0056] S1. Add 10 g of nano-erbium oxide with a particle size of 50 nm into a reactor, then add 50 mL of deionized water, and stir ultrasonically at room temperature for 30 min to obtain a nano-erbium oxide dispersion;
[0057] S2. Add 50 mL of 0.05 mol / L tannic acid solution to the reactor of step S1, and use phosphate buffer to adjust the pH of the reaction system to 8.0, then heat to 80°C, stir and react at a speed of 2000 r / min for 8 h. After the reaction is completed, filter, then wash the solid product twice with deionized water to remove unloaded polyphenol compounds, and finally dry at 60°C for 12 h to obtain a bifunctional gypsum admixture.
[0058] Example 5
[0059] Compared with Example 1, the only difference is that the nano-erbium oxide is replaced by nano-bismuth oxide.
[0060] Example 6
[0061] Compared with Example 5, the only difference is that 50 mL of 0.03 mol / L tannic acid solution is replaced with 50 mL of 0.03 mol / L gallic acid solution.
[0062] Example 7
[0063] Compared with Example 5, the only difference is that the particle size of nano-bismuth oxide is 50 nm.
[0064] Example 8
[0065] Compared with Example 4, the only difference is that the nano-erbium oxide is replaced by nano-bismuth oxide.
[0066] Comparative Example 1
[0067] Nano-erbium oxide with a particle size of 200 nm is used as gypsum admixture.
[0068] Comparative Example 2
[0069] Compared with Example 3, the only difference is that the particle size of the nano-erbium oxide is 500 nm.
[0070] Comparative Example 3
[0071] Compared with Example 5, the only difference is that the reaction temperature is 25°C and the reaction time is 3 h.
[0072] Comparative Example 4
[0073] Compared with Example 7, the only difference is that the particle size of nano-bismuth oxide is 500 nm.
[0074] Test example
[0075] Test of the retarding properties of the admixtures prepared in Examples 1 to 8 and Comparative Examples 1 to 4
[0076] The admixtures prepared in Examples 1 to 8 and Comparative Examples 1 to 4 were used to prepare X-ray shielding gypsum in the following manner:
[0077] 10%, 20%, 30%, 40% and 50% of the admixture (based on the mass of X-ray shielding gypsum) were respectively dispersed in 30% of deionized water (based on the sum of the mass of gypsum powder and admixture), and then fully mixed with gypsum powder to make gypsum slurry, which was then poured into a mold with a diameter of 6 cm and a thickness of 1 cm and waited for complete solidification to obtain gypsum samples. The initial setting time of the gypsum slurry was recorded, and the compressive strength and X-ray shielding properties of the gypsum samples were tested.
[0078] The preparation method of blank gypsum samples is as follows:
[0079] Take an appropriate amount of gypsum powder, pour it into 30% deionized water (based on the mass of gypsum powder), mix it thoroughly to make gypsum slurry, and then pour it into a mold with a diameter of 6 cm and a thickness of 1 cm and wait for it to completely solidify to obtain a blank gypsum sample.
[0080] In the test example, the X-ray shielding performance of the gypsum material was evaluated by the shielding efficiency, and the calculation method is shown in formula (1):
[0081]
[0082] Wherein, AE is the radiation shielding efficiency of gypsum material, %; D0 is the initial X-ray dose, μGy / s; D π It is the remaining X-ray dose after passing through the shielding material, μGy / s.
[0083] The X-ray emission device used to test the shielding performance of gypsum materials is a unidows E dosimeter. The energy range of the effective X-ray photons tested is 20~120 keV. The ray voltage refers to the national standard JJG 393-2003 and the international standard ISO4037-1:1996. Figure 5 shown.
[0084] The initial setting time and compressive strength are determined in accordance with GB / T 17669.4-1994 "Determination of physical properties of building gypsum paste" and GB / T 17669.3-1994 "Determination of physical properties of building gypsum paste".
[0085] Table 1 Initial setting time of gypsum with different admixture addition amounts (min)
[0086]
[0087] It can be seen from the initial setting time data in Table 1 that the retarding effect of the gypsum admixture provided by the present invention on gypsum is affected by the amount of addition, reaction conditions, nanoparticle size, and plant polyphenol type. Specifically, the retarding effect of Examples 1-8 on gypsum is enhanced with the increase of the amount of addition, and the initial setting time of gypsum can be extended to 80 min at most. Compared with Example 5, the retarding effect of Comparative Example 3 on gypsum is greatly reduced. This is because the reaction temperature during the preparation of Comparative Example 3 is 25 ° C and the reaction time is 3 h, which leads to insufficient reaction between plant polyphenols and nanoparticles, and only a small amount of plant polyphenols are covered on the surface of the nanoparticles. In addition, there is a large gap between the retarding effects of Comparative Example 2 and Example 3, with a maximum difference of 33 min at the same addition amount. The reason is that the nanoparticles used in Comparative Example 2 have a particle size of 500 nm, while the nanoparticles used in Example 3 have a particle size of 50 nm. Under the same conditions, nanoparticles with smaller particle sizes are more likely to react with plant polyphenols, and the surface can be covered with more plant polyphenols. By comparing Example 1 with Example 2, and Example 5 with Example 6, it can be seen that the admixture prepared with tannic acid has a better retarding property than the admixture prepared with gallic acid. This is because tannic acid is a complex phenolic compound with a large molecular structure and contains a large number of phenolic hydroxyl groups, while gallic acid is a simple phenolic acid and is one of the constituent units of tannic acid. It is worth noting that the initial setting time of gypsum is accelerated with the increase of the addition amount of Comparative Example 1, and the fastest solidification time is 1 minute. This is because the metal oxide nanoparticles form more crystal nuclei inside the gypsum, which promotes the growth and solidification of gypsum crystals.
[0088] Table 2 Effect of admixture amount on compressive strength (MPa)
[0089]
[0090] Table 3 Effect of admixture amount on flexural strength (MPa)
[0091]
[0092] It can be seen from the compressive strength data of Table 2 and the flexural strength data of Table 3 that the compressive strength of blank gypsum is 21.7 MPa and the flexural strength is 7.1 MPa. On the whole, after adding the admixture of Example 1-8, the compressive strength of gypsum decreases with the increase of addition, but the minimum can still be maintained at more than 16 MPa, and the flexural strength can be maintained at a higher level. Combined with the data in Table 1, it can be explained that the admixture provided by the present invention not only shows excellent slow setting performance to gypsum, but also ensures that gypsum has higher mechanical strength. It is worth noting that the compressive strength of gypsum is higher than that of blank gypsum when the addition is 10%, and the flexural strength of gypsum is higher than that of blank gypsum when the addition is 10% and 30%, because the nanoparticles fill the pores between gypsum crystals, improve the compactness of gypsum, thereby enhancing the mechanical strength of gypsum.
[0093] Figure 1 The SEM images of the gypsum after adding different proportions of the admixtures of Example 3 and Example 4 are shown in FIG. Figure 1 It can be seen that nanoparticles can fill the micropores in the gypsum matrix, reduce the generation and expansion of microcracks, improve the density of gypsum crystals, and thus improve the mechanical strength. In addition, a strong chemical or physical bond is formed between the nanoparticles and the gypsum crystal interface, which enhances the overall strength of the composite material.
[0094] Figure 2 Figure a is the Fourier transform infrared spectrum of erbium oxide nanoparticles before and after modification with tannic acid. The vibration peaks of the functional groups corresponding to the tannic acid molecules appear in the spectrum after modification. Figure 1 Figure b is the X-ray diffraction of erbium oxide nanoparticles before and after modification with tannic acid. As shown in the figure, the intensity and position of the diffraction peaks corresponding to the nanoparticles did not change significantly before and after the modification, indicating that the tannic acid coating layer is an amorphous structure and the crystal morphology of the nanoparticles is not changed after coating. Figure 1 In the figure, c is the TSI value of the nanoparticles dispersed in water for one hour before and after modification. Compared with before modification, the TSI value of the modified nanoparticles in water is significantly reduced, indicating that their dispersibility and stability in water are greatly enhanced. Figure 1 Figure d is a digital photo of the aqueous dispersion of nanoparticles before and after modification after standing for 8 hours. From left to right, they are Comparative Example 1, Example 3, and Example 4. The boxed part in the figure is the supernatant. The unmodified nanoparticles agglomerated and precipitated at the bottom of the bottle, while the modified nanoparticles are still evenly dispersed in the water.
[0095] Figure 3TEM images of Example 3, wherein a is BF-TEM and b is HAADF-STEM; Figure 4 TEM images of Example 4, wherein a is BF-TEM and b is HAADF-STEM. Figure 3~Figure 4 As shown, the plant polyphenol layer is obviously and evenly coated on the surface of the nanoparticles in Examples 3 and 4. Relatively speaking, since the reaction temperature in Example 4 is higher, the reaction time is longer, and the concentration of plant polyphenols used is higher, the coating effect of plant polyphenols on the surface of the nanoparticles is better.
[0096] Figure 5 Schematic diagram of the X-ray shielding efficiency test device.
[0097] Figure 6 The X-ray shielding efficiency of the gypsum with the additives of Examples 1 to 4 added, wherein a is Example 1, b is Example 2, c is Example 3, and d is Example 4. As can be seen from the figure, the gypsum with the addition of Examples 1 and 2 has excellent ray shielding performance, and the shielding efficiency of X-rays with an energy of 20 to 80 keV can reach more than 50%. However, the shielding efficiency of Example 2 is slightly lower than that of Example 1 as a whole. In the low energy range of 20 to 40 keV, the difference between the two is not obvious, about 1 to 3%. As the energy of the rays increases, the difference in shielding efficiency between the two gradually increases, with a maximum difference of 8%. The reason for this difference is that the plant polyphenol selected in Example 2 is gallic acid, and the active groups in the gallic acid molecules are far less than those in the tannic acid molecules, so the dispersibility and stability of the nanoparticles wrapped by gallic acid are poor. The gypsum with the addition of Examples 3 and 4 can reach a shielding efficiency of more than 60% for X-rays with an energy of 20 to 80 keV, which is higher than that of Examples 1 and 2. This is because the nanoparticles used in Examples 3 and 4 have a particle size of 50 nm, which is smaller than the 200 nm used in Examples 1 and 2. When radiation photons collide with nanoparticles, nanoparticles with smaller particle sizes are more likely to collide effectively, and the number of collisions is relatively large. Therefore, the use of nanoparticles with smaller particle sizes can enhance the shielding performance of the material. It is worth noting that the shielding efficiency of Example 4 is slightly higher than that of Example 3. This is because the preparation of Example 4 is higher than that of Example 3 in terms of reaction temperature and reaction time, so the surface of the nanoparticles in Example 4 is covered with more plant polyphenols.
[0098] Figure 7The figure shows the X-ray shielding efficiency of the gypsum added with Example 1 and Comparative Example 1, where a is 10% added, b is 30% added, and c is 50% added. It can be seen from the figure that the shielding performance of the gypsum added with Comparative Example 1 is lower than that of the gypsum added with Example 1 as a whole, and the difference in shielding performance becomes more obvious as the amount added increases. For example, in the ray energy range of 80~120keV, when the amount added is 50%, the shielding efficiency of Example 1 is more than 5% higher than that of Comparative Example 1. The reason for this gap is that the nanoparticles of Comparative Example 1 have not been treated in any way, and their dispersibility and stability in gypsum crystals are poor. This also further illustrates that the dispersibility and stability of nanoparticles in gypsum crystals are important factors affecting shielding performance.
[0099] Figure 8 The X-ray shielding efficiency of gypsum added with Example 3 and Comparative Example 2, where a is 10% addition, b is 30% addition, and c is 50% addition. As can be seen from the figure, overall, the shielding performance of the gypsum added with Comparative Example 2 is lower than that of the gypsum added with Example 3, and as the addition amount increases, the difference in shielding performance in the high energy segment is more obvious. At 20~60 keV, the shielding efficiency of Example 3 is 1~3% higher than that of Comparative Example 2. At 80~120 keV, the shielding efficiency of Example 3 is 3~5% higher than that of Comparative Example 2. The reason is that the nanoparticles in Comparative Example 2 have a larger particle size of 500 nm, while those in Example 3 are 50 nm. This further illustrates that adding nanoparticles with smaller particle sizes to gypsum crystals has better shielding performance than adding nanoparticles with larger particle sizes.
[0100] Fig. 9 The X-ray shielding efficiency of gypsum with additives of Examples 5 to 8, wherein a is Example 5, b is Example 6, c is Example 7, and d is Example 8. As can be seen from the figure, the gypsum with additives of Examples 5 and 6 has excellent ray shielding performance, and the shielding efficiency of X-rays with an energy of 20 to 60 keV can reach more than 50%. However, the shielding efficiency of Example 6 is about 3% lower than that of Example 5 as a whole. This is because the plant polyphenols used in Example 6 are gallic acid, and those used in Example 5 are tannic acid. This further illustrates that the active groups of plant polyphenols affect the dispersibility and stability of nanoparticles, thereby affecting the ray shielding performance of the material. The gypsum with additives of Examples 7 and 8 has excellent ray shielding performance, and the shielding efficiency of X-rays with an energy of 20 to 80 keV can reach more than 40%, and the shielding efficiency of X-rays with an energy of 100 to 120 keV can reach more than 30%. When the addition amount is 50%, the shielding efficiency can reach more than 70%.
[0101] Fig.10The X-ray shielding efficiency of the gypsum added with Example 5 and Comparative Example 3, wherein a is 10% addition, b is 30% addition, and c is 50% addition. As can be seen from the figure, the shielding performance of the gypsum added with Comparative Example 3 is lower than that of the gypsum added with Example 5 at the same addition amount and the same ray energy, with a maximum difference of more than 5%. This is because the reaction temperature of Comparative Example 3 is too low and the reaction time is too short, resulting in a large amount of plant polyphenols not covering the surface of the nanoparticles. This also further illustrates that the reaction conditions are an important factor affecting the performance of the admixture.
[0102] Fig.11 The X-ray shielding efficiency of the gypsum added with Example 7 and Comparative Example 4, where a is 10% addition, b is 30% addition, and c is 50% addition. As can be seen from the figure, the shielding performance of the gypsum added with Comparative Example 4 is lower than that of the gypsum added with Example 7, and as the addition amount increases, the difference in shielding performance in the high energy segment is more obvious, with a maximum difference of more than 7%. This is because the nanoparticles in Comparative Example 4 have a larger particle size of 500 nm, while those in Example 7 are 50 nm. This further illustrates that adding nanoparticles with smaller particle sizes to gypsum crystals has better shielding performance than adding nanoparticles with larger particle sizes.
[0103] It is worth noting that the shielding efficiency of Examples 5-8 and Comparative Examples 3-4 in the energy range of 40-80 keV is not good, and with the increase of the radiation energy, the shielding efficiency decreases rapidly. The essence of the Compton effect and photoelectric effect between the shielding material and the X-ray is the effect of the extranuclear electrons of the nanoparticles and the radiation photons. Therefore, the energy of the K and L absorption edges of the extranuclear electron layer of the element significantly affects the radiation shielding performance of the material, and the shielding effect on the radiation with similar energy to its absorption edge is significant. The two absorption edge energies of the bismuth element are close to 20 keV and 90 keV, which is quite different from 40-80 keV, which leads to the poor shielding efficiency of bismuth against X-rays in this energy range.
[0104] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a dual-functional gypsum admixture based on plant polyphenols-nanoparticles, characterized in that the steps include: Plant polyphenols are added to the metal oxide nanoparticle dispersion, the pH is adjusted to 7.5-8.0, and after the reaction, the dual-functional gypsum admixture is obtained by filtering, washing and drying.
2. The preparation method according to claim 1, characterized in that The metal oxide nanoparticles in the metal oxide nanoparticle dispersion include at least one of erbium oxide nanoparticles, bismuth oxide nanoparticles, tungsten oxide nanoparticles, lanthanum oxide nanoparticles, tin oxide nanoparticles and cesium oxide nanoparticles; and / or, The particle size of the metal oxide nanoparticles is 50-200 nm.
3. The preparation method according to claim 1, characterized in that: The concentration of the metal oxide nanoparticles in the metal oxide nanoparticle dispersion is 5-10 wt %; and / or, The metal oxide nanoparticle dispersion is prepared by dispersing metal oxide nanoparticles in water.
4. The preparation method according to claim 1, characterized in that: The plant polyphenols include tannic acid, gallic acid or catechin acid; and / or, The concentration of the plant polyphenols in the reaction system is 0.03-0.05 mol / L.
5. The preparation method according to claim 1, characterized in that: The pH value is adjusted to 7.5-8.0 by using PBS buffer solution to adjust the pH value; and / or, The reaction temperature is 60-80°C, the reaction time is 5-8 hours, and the reaction speed is 2000 r / min.
6. The preparation method according to claim 1, characterized in that: The washing is washing with water at least twice; and / or, The drying temperature is 40-60°C and the drying time is 8-12 hours.
7. The dual-functional gypsum admixture obtained by the preparation method as claimed in claim 1.
8. Use of the dual-functional gypsum admixture as claimed in claim 7 in the preparation of gypsum.
9. An X-ray shielding plaster, characterized in that: In terms of mass percentage, the components include: 50-90% gypsum powder and 10-50% of the dual-functional gypsum admixture according to claim 7.
Citation Information
Patent Citations
Radiation-proof putty powder and preparation method thereof
CN103525153A
Rare-earth nuclear-radiation-proof mortar and preparation method of rare-earth nuclear-radiation-proof mortar
CN105645865A
Method for modifying building gypsum product from phosphogypsum
CN108191364A
Concrete admixture and preparation method
CN108503251A
Anti-radiation sulphoaluminate cement-base nuclear power concrete for high-latitude regions
CN109592952A
Cited By
Preparation method of lysine-tannic acid compound retarder and gypsum-based building material
CN121948861A
Preparation method of lysine-tannic acid complex retarder and gypsum-based building material
CN121948861B